Phương pháp gần đúng giải bài toán truyền sóng ứng dụng trong thăm dò địa chấn - Quảng, Lê Xuân (Journal of Computer Science and Cybernetics, 2016)
In this work we consider two models of seismic waves. We use projection method and Ray-methods for solving the problems.